ANALISIS EKONOMI PROSPEKTIF PENGEMBANGAN KPH DAMPELAS TINOMBO BERBASIS PHBM DI DESA KARYA MUKTI - Fitrawan, Rahmat; Umar, Syukur; Irmasari, Irmasari (Universitas Tadulako, 2014)
The research was conducted from April to June 2013 at the village of Karya Mukti, Damsol district, Donggala regency. The research aimed to know the development prospective of forest management based community (PHBM) regarding community incoment and its respective factors, and to compare financial aspect of rubber (Hevea brassiliensis) and cacao (Theobroma cacao L.) plants before and after KPH Dampelas Tinombo development. The research use Regresi analysis method and Net Present Value (NPV). The result showed that equtian of Regresi Y = -16890,7 + 314,9422X1 – 303,526X2 + 2042,522X3 + 20017,94X4 – 478,691X5 and the factor of X4 (amount of production of farm residing in area KPH) influential obvious of the community income. The result showed that NPV of rubber was IDR 269.096.747 while NPV of cacao was IDR 147.754.688. Hence the level community income were IDR 46.977.778, and IDR 4.340.000 year-1for each respondent, for rubber and cacao production, respectively. Key words: economic analysis, development prospective, KPH Dampelas Tinombo, Income of community